(3CShGb GdChQGb GdeGdjI (B:s (3GdHhQUI (B/s - (3MSjf, YUGes ((3YeGf(B: s (3OGQ CSGeI ddfTQ hGdJhRjY(B, s, 2010)
(3fTCI GdGShGb GdeGdjI , eaghe CShGb GdGhQGb GdeGdjI , HhQUI Gdbje GdefbhGI , caGAI h eDTQGJ CShGb GdGhQGb GdeGdjI cjajI HfGA GdeDTQGJ , GdefJLGJ GdeUQajI , GdHVGYI GdeJOGhdI aj GdShb , BdjI Yed GdHhQUI , HfjI GdShb GdeGdjI , GdJOhjQ h TQcGJ GdeVGQHI , GdJLejY , CSHGH GQJaGY CSYGQ GdCSge h GfNaGVgG , feGPL GdeNWWGJ GdHjGfjI ddCSge , COhGJ Shb QCS GdeGd , GdJMdjd h GfhGYg , JMdjd HhQUGJ GdefWbI GdYQHjI , WQjbI Jbjje GdCSge , GdGSJKeGQ aj GdCShGb GdeGdjI UfGOjb GdGSJKeGQ , GdeVGQHI aj Shb GdChQGb GdeGdjI h GdGSJKeGQ , GSJQGJjLjI GdeVGQHI , YTQI CNWGA ddeVGQHjf aj GdGSge , hbaGJ eY GdeVGQHI GdjhejIs
Keywords: (3GdESJKeGQs; (3GdChQGb GdeGdjIs; (3GdHhQUGJs